(untitled) (Physical Education, Health and Social Sciences, 2025)
Microbial enzymes have revolutionized food processing by offering efficient, sustainable, and scalable biocatalytic solutions for enhancing product quality, texture, flavor, and shelf life. This review explores the shift from traditional animal and plant-derived enzymes to microbial sources, driven by advancements in industrial biotechnology, fermentation technologies, and genetic engineering. Key enzyme classes, including proteases, glycosyl hydrolases, lipases, and extremozymes, are discussed in the context of their applications in dairy, baking, starch conversion, and beverage industries. The global market for food enzymes is projected to grow from USD 4.6 billion in 2024 to USD 6.7 billion by 2030, fueled by consumer demand for clean-label products and natural processing aids. Challenges in production methods (submerged vs. solid-state fermentation), enzyme stabilization through immobilization and directed evolution, and regulatory frameworks (FDA GRAS vs. EU EFSA) are analyzed. Emphasis is placed on sustainability, with enzymes enabling valorization of agri-food byproducts and green extraction technologies. Future prospects highlight the integration of AI-driven engineering and extremozyme discovery to address emerging industrial needs, positioning microbial enzymes as pivotal for a circular economy in food systems.